Destination management organizations (DMOs) and Digital Natives: the neglected “informal expertise” in web 2.0 implementation and social media presence. Insights from the Italian Friuli Venezia Giulia DMO - Gon, M.; Pechlaner, Harald; Marangon, F. (2016)
The present paper wishes to investigate the perspective of Digital Natives (DNs), described in literature as “informal experts”, in respect of digital strategies’ implementation of destination management organizations (DMOs). In particular, focus groups of students and workers in the tourism field were asked to browse and discuss the website and social media presence of an Italian regional DMO (i.e. PromoTurismoFVG). Comments were collected and analyzed with the GABEK/Winrelan method for qualitative analysis. Results confirmed the DMO’s adoption of a digital format but with limited social and consumer-generated-contents (CGC). DNs recognized the implementation of a Web 2.0 destination site in a rather traditional marketing mix strategy. Furthermore DMO websites and social media (SM) (i.e., Facebook, Instagram, Twitter and YouTube) content analysis showed that the DMO lacks products and offers for the young market segment. The combination of limited social content and the weak attention to youth market makes the current digital DMO not attractive enough to the digital natives. The work highlights the importance on focusing on DN “informal expertise” in the planning and development of digital strategies, DMO websites and SM presence. Their proved social media knowledge and digital competences have to be considered as a key opportunity for DMOs and for the improvement of the destination marketing strategies. This research contributes to the academic discussion on SM/Web 2.0 implementation in destination management, by presenting an exploratory study on DNs’ informal expert perspective supported by the use of GABEK/Winrelan as an innovative method.